A multifunctional material with distinct mechanochromic and piezochromic properties: π-stacking in play. (30th November 2021) - Ding, Zeyang; Lu, Tong; Bi, Changjiang; Li, Bao; Zhang, Shi-Tong; Xu, Weiqing; Jiang, Shimei
Abstract : Opposite emission variations under anisotropic shearing and isotropic pressure are observed, which are attributed to the destruction and reinforcement of molecular π–π interactions, respectively. Abstract : Controlling different types of forces to achieve materials with different emission responses remains a challenge. In this work, polymorphic organic crystals with blue (1-B) and green (1-G) emission based on N -(4-(1-cyano-2-phenylvinyl)phenyl)benzamide are prepared. In 1-G, the molecules form continuous π-stacking through π–π interactions, while no π–π interactions are found in 1-B. When shearing and UV irradiation are applied to 1-G, the emission blue shifts to a shorter wavelength region. Experimental investigations show that the shearing causes a crystal-to-crystal transition from 1-G to 1-B, while the UV irradiation promotes the occurrence of a photocycloaddition reaction. The external and internal factors contribute to the destruction of molecular π-stacking. In sharp contrast, under isotropic pressing, 1-G exhibits an obviously red-shifted emission owing to the formation of a tighter packing structure where the π–π interactions are reinforced. This work not only regulates molecular packing and controls emission variations in a versatile manner but also enriches the insights into mechanochromic and multifunctional materials.